Conceptual Design of Geophysical Microsatellite - Matviyenko, S.A. (Science and Innovation, 2024)
The research covers the issues related to the measurement of Earth gravitational field (EGF) parameters in the space. The radiophysical method for the measurement of gravitational frequency shift of electromagnetic radiation using existent GNSS and its two variants have been developed. A geophysical microsatellite has been designed to implement the radiophysical method of EGF measurement and to enable the researchers to monitor the Earth plasmasphere and mag netosphere.